ULF Waves Modulating and Acting as Mass Spectrometer for Dayside Ionospheric Outflow Ions. Issue 15 (8th August 2019) - Liu, Z.‐Y.; Zong, Q.‐G.; Zhou, X.‐Z.; Hao, Y. X.; Yau, A. W.; Zhang, H.; Chen, X.‐R.; Fu, S. Y.; Pollock, C. J.; Le, G.; Ergun, R. E.; Lindqvist, P.‐A.
Abstract: Ionospheric outflow has been shown to be a dominant ion source of Earth's magnetosphere. However, most studies in the literature are about ionospheric outflow injected into the nightside magnetosphere. We still know little about ionospheric outflow injected into the dayside magnetosphere and its further energization after it enters the magnetosphere. Here, with data from Magnetospheric Multiscale mission, we report direct observations of the modulation of dayside ionospheric outflow ions by ultralow frequency (ULF) waves. The observations indicate that the modulation is mass dependent, which demonstrates the possibility of using ULF waves as a mass spectrometer to identify ion species. Moreover, the measurement suggests that polarization drift may play a role in O + modulation, which may lead to a true acceleration and even nonadiabatic behavior of O + . This interaction scenario can work throughout the whole magnetosphere and impact upon the plasma environment and dynamics. Key Points: Interaction between ULF waves and ionospheric outflow ions injected into the dayside magnetosphere was observed by MMS ULF waves can serve as an auxiliary diagnostic for the detection of ionospheric outflow ions and inference of their mass species Polarization drift plays a role in the modulation of oxygen ions